2022
DOI: 10.1177/17588359221080298
|View full text |Cite
|
Sign up to set email alerts
|

Atezolizumab and bevacizumab in patients with advanced hepatocellular carcinoma with impaired liver function and prior systemic therapy: a real-world experience

Abstract: Objective: Evaluation of the efficacy and safety of atezolizumab/bevacizumab in a real-world HCC cohort, including patients with impaired liver function and prior systemic therapy. Methods: Retrospective analysis of 147 HCC patients treated with atezolizumab/bevacizumab at six sites in Germany and Austria. Results: The overall response rate and disease control rate were 20.4% and 51.7%, respectively. Seventy-three patients (49.7%) met at least one major exclusion criterion of the IMbrave150 trial (IMbrave-OUT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 68 publications
(78 reference statements)
3
42
0
1
Order By: Relevance
“…Many realworld reports have defined the clinical efficacy and safety of the new standard regimen and also explored the efficacy of the combination for these patients who cannot merit the original eligibility criteria of IMbrave 150 trail. The efficacy and safety based on real world data (RWD) were consistent with those reported from IMbrave 150 trial (7,8). A report of 147 HCC patients treated with atezolizumab/bevacizumab in Germany and Austria demonstrated that prior systemic treatment did not affect OS or PFS, which reflected our data presented here.…”
Section: Discussionsupporting
confidence: 88%
“…Many realworld reports have defined the clinical efficacy and safety of the new standard regimen and also explored the efficacy of the combination for these patients who cannot merit the original eligibility criteria of IMbrave 150 trail. The efficacy and safety based on real world data (RWD) were consistent with those reported from IMbrave 150 trial (7,8). A report of 147 HCC patients treated with atezolizumab/bevacizumab in Germany and Austria demonstrated that prior systemic treatment did not affect OS or PFS, which reflected our data presented here.…”
Section: Discussionsupporting
confidence: 88%
“…A recent real-world study has reported that the median PFS is significantly shorter in patients who did not meet the IMbrave150 eligibility criteria than in patients who met the criteria [PFS: 3.7 months vs. 8.7 months] [ 11 ]. Although more than half of patients did not meet the eligibility criteria for IMbrave150 in this study, median PFS was similar between patients who did and those who did not meet the criteria (PFS 6.5 months (95% CI; 3.7–NE months) vs. 6.9 (95% CI; 4.2–8.9 months)).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has revealed that OS and PFS are significantly shorter in patients with Child-Pugh B and C than in patients with Child-Pugh A [ 11 , 23 ]. In this study, the PFS and treatment response were similar between patients with Child-Pugh A and B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCC is associated with high mortality, morbidity, and poor prognosis. Chemotherapy is the standard treatment for HCC [ 2 ], and the combination of atezolizumab and bevacizumab is the first-line treatment for advanced HCC [ 3 ]; however, the clinical safety of this combination has not yet been fully evaluated in patients [ 4 ]. Therefore, there is an urgent need to explore and discover new drugs with fewer toxic side effects to treat patients with HCC.…”
Section: Introductionmentioning
confidence: 99%